Aflatoxin B1-Adsorbing Capability of Pleurotus eryngii Mycelium: Efficiency and Modeling of the Process - Haidukowski, Miriam; Casamassima, Eliana; Cimmarusti, Maria Teresa; Branà, Maria Teresa; Longobardi, Francesco; Acquafredda, Pasquale; Logrieco, Antonio; Altomare, Claudio (Frontiers in Microbiology, 2019)
Aflatoxin B1 (AfB1) is a carcinogenic mycotoxin that contaminates food and feed worldwide. We determined the AfB1-adsorption capability of non-viable Pleurotus eryngii mycelium, an edible fungus, as a potential means for removal of AfB1 from contaminated solutions. Lyophilized mycelium was produced and made enzymatically inert by sterilization at high temperatures . The material thus obtained was characterized by SEM microscopy with regard to the morpho-structural properties of the mycotoxin-adsorbing surfaces. The active surfaces appeared rough and sponge-like. The AFB1-mycelium system reached the equilibrium at 37 °C, 30 minutes and pH 5 -7, conditions that are compatible with the gastro-intestinal system of animals. The system remained stable for 48 h at room temperature, at pH 3, pH 7 and pH 7.4. A thermodynamic study of the process showed that this is a spontaneous and physical adsorption process, with a maximum of 85 ± 13 % of removal efficiency of AfB1 by P. eryngii mycelium. These results suggest that biosorbent materials obtained from the mycelium of the mushroom P. eryngii could be used as a low-cost and effective feed additive for AfB1 detoxification.